Analisis dan Perancangan Sistem Informasi Rekam Medis Pada Puskesmas Simpang Timbangan Indralaya - Fransiska Prihatini Sihotang (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2015)
Medical record is a file containing records and documents about the patient’s identity, examination, treatment, medical action, and other services that have been administered to patients. Management need a medical record file for planning, controlling, and evaluating the quality of care. Puskesmas (local medical center) is a technical unit of the District/City Health Office held responsible for health development in one or some districts. Puskesmas has a fairly complex service such as outpatient services, inpatient, laboratory tests, and pharmacy. The purpose of this research is to design an integrated medical record information systems at Puskesmas Simpang Timbangan Indralaya to repair the old system. This study used FAST as system development, and to colect the data used interview, observation, and literature study. The results of this study is the design of medical record information system on Puskesmas Simpang Timbangan Indralaya consisting of inpatient services, outpatient services, laboratory management, pharmacy management, and medical reports. The design is generated in the form of DFD, ERD, decomposition diagrams, application design interface, report design, and network architecture design.